2018
DOI: 10.1371/journal.pcbi.1006047
|View full text |Cite
|
Sign up to set email alerts
|

Use of temperature to improve West Nile virus forecasts

Abstract: Ecological and laboratory studies have demonstrated that temperature modulates West Nile virus (WNV) transmission dynamics and spillover infection to humans. Here we explore whether inclusion of temperature forcing in a model depicting WNV transmission improves WNV forecast accuracy relative to a baseline model depicting WNV transmission without temperature forcing. Both models are optimized using a data assimilation method and two observed data streams: mosquito infection rates and reported human WNV cases. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Higher temperatures have been also associated with shorter extrinsic incubation periods, accelerating WNV transmission by the mosquito vector 54,55 . Interestingly, temperature has also been suggested as a variable that can increase the predictive power of WNV forecast models 56 . The impact of temperature that we reveal here on both dispersal velocity and viral genetic diversity is particularly important in the context of global warming.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures have been also associated with shorter extrinsic incubation periods, accelerating WNV transmission by the mosquito vector 54,55 . Interestingly, temperature has also been suggested as a variable that can increase the predictive power of WNV forecast models 56 . The impact of temperature that we reveal here on both dispersal velocity and viral genetic diversity is particularly important in the context of global warming.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis used 2 forecasting systems, a baseline model with no temperature forcing 13 and a model that includes environmental forcing (average daily temperature [ie, climatology] for the region) by accounting for temperature modulation of the extrinsic incubation period for mosquitos. 12 Both models used a standard susceptible-infected-recovered epidemiological construct and were optimized using a data assimilation method and 2 observed data streams: mosquito infection rates and reported human WNV cases. The methodological approach and its application in real-time infectious diseases forecasting are briefly described later in this section.…”
Section: Methodsmentioning
confidence: 99%
“…For further details on the validation of the WNV model-inference forecasting systems, see the articles by DeFelice et al 12 , 13 The remainder of the Methods section describes how we used the observed reporting lags from the 2017 WNV season to evaluate the associations of reporting delays with forecast accuracy for 110 historical outbreaks. 12 We followed the Consolidated Health Economic Evaluation Reporting Standards ( CHEERS ) 21 reporting guideline to report the difference in likelihood of an accurate forecast given current reporting lags relative to ideal reporting of all data in real time. This research received institutional review board approval from Columbia University, which waived requirements for participant informed consent because the study used deidentified data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations